- Den teologiske modtagelse af Verdenskrøniken 1812 - Pedersen, Kim Arne (Grundtvig-studier, 2013)
Den teologiske modtagelse af Verdenskrøniken 1812[The Theological Reception of Grundtvig’s World Chronicle 1812]By Kim Arne Pedersen Taking as its starting point William Michelsen’s characterization of the Danish literary and artistic Golden Age and of Grundtvig’s position in Danish intellectual life after the publication in 1812 of Kort Begreb af Verdens Krønike i Sammenhæng (A Brief View of the World Chronicle in Context, VK 1812), this paper analyses Grundtvig’s ensuing discussions with theologians up until 1815. Grundtvig’s antagonists all bore the mark of Enlightenment theology while at the same time each taking up a different position, and the analysis shows the need to rework Michelsen’s stylization of Grundtvig’s isolation after 1812 as a result predominantly of his antagonism to German idealistic philosophy.Grundtvig’s dispute with the vicar Johan Harder (1768-1831) is the first to be considered. Harder was characterized by a Kantian rationalism from which Grundtvig had dissociated himself after having read Kant’s treatise Die Religion innerhalb der Grenzen der blossen Vernunft. In his correspondence with the curate Andreas Krag Holm (1767-1851), Grundtvig encountered a defence of the theological principle of accommodation, i.e. the idea that Christ in his earthly life had adapted himself to the notions of his contemporaries, originally forwarded by J. G. Zollikofer (1730-88).The most important discussion caused by VK 1812 is the one between Grundtvig and professor of Divinity Jens Møller (1779-1833), who stood for an early supranaturalistic theology of a Wolffian stamp combined with respect for the historical revelation. Grundtvig’s own historically based theology of revelation would seem to make a mutual approach possible, but Møller’s publishing of an article in his periodical Theologisk Bibliothek (Theological Library) by the Kantian-rationalistic supranaturalist H. G. Tzschirner (1778-1828) was cause for controversy. The fact that Møller admitted historical-critical reason to play an essential part in theology and did not assume reason to be determined exclusively by faith caused Grundtvig to criticize him, even though he acknowledged Møller as a fellow Christian. Thus, Grundtvig’s evaluation of Møller is reminiscent of his characterization in VK 1812 of the German supranaturalist F. V. Reinhard (1753- 1812).Grundtvig’s discussions with contemporary theologians place his controversies with writers influenced by idealism such as the natural scientist H. C. Ørsted (1777-1851) and the historian Christian Molbech (1783-1857) in a largercontext; in particular this is true in relation to Ørsted.Grundtvig was positive yet still guarded in his stimation of Kant’s setting a limit to human knowledge in Kritik der reinen Vernunft, but he rejected the concept of faith as based on the autonomy of reason as it had been proposed by Kant in his works on religion. Grundtvig’s sympathy for Kant’s assertion of the limits of reason might seem to bring him close to a Kantian supranaturalism, however, Grundtvig’s emphasis on the unconditional dependence of reason on faith separates him from the thinking of all other contemporary academic theologians. In his periodical Danne-Virke, Grundtvig stuck to this evaluation of Kant in an argumentation for reason as ruled by faith.